Peran Pembimbing Kemasyarakatan Dalam Penanganan Pelaku Penyebaran Konten Pornografi oleh Anak Dibawah Umur - Suparman S (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Technology can have both good and bad effects depending on how each person uses the technology. There are minors who abuse technology in cyberspace so as to cause criminal acts (Cybercrime), one of them is revenge porn. One of the competent parties to be presented in cases of Children Who Are Faced the Law is Probation Officer. Probation Officers have tasks and functions to facilitate children who commit criminal offenses. There are 3 (three) stages of dealing with Children Who Are Faced the Law by Probation Officer, i.e. before the trial, during the trial and after the trial. The treatment process carried out by the Probation Officer can hopefully make a change to the Children Who Are Faced the Law to have a better direction and have a deterrent effect on the actions they take, especially about pornographic content which has a very strong effect on the victim. Probation Officers have an important task and role in handling cases of children in conflict with the law or in this research is the case of children who spread pornographic content without the consent of the other party (Revenge Porn). This Probation Officer has protected Children Who Are Faced the Law based on regulations.